Geology and karst geomorphology of Kampung Kala Baru, Gua Musang, Kelantan - Wan Nur Syahirah W Abd Muhaimi (2019)
This study focused on Geological and Geomorphologic Mapping-based method to identify the karst formation/landforms. The study area located at Kampung Kala Baru, Gua Musang, Kelantan. The land of this area is mostly covered by karst limestone formation. The karst formation is one of the indicators of environmental history and landscape evolution. There is lack of study about karst geomorphology at Gua Musang. The karst landform of Kampung Kala Baru can give many advantages toward the economic development. The main purpose of this study is to update and produce a geological map, to identify karst formation/landform and to produce karst geomorphologic map of Kampung Kala Baru. The geological mapping was conducted to observe the geology in the study area. The study area is included in Gua Musang formation and consists of four types of lithologies; granite, limestone, tuff and metasediment. There are three types of karst formation/landforms has been found and identified at Kampung Kala Baru which are surface karsts, subsurface karsts and surficial landforms. Geomorphologic mapping was done with the help of satellite imagery to see the boundary of the karst. Field observation will help for further interpretation of the process and characteristics that own by the karst. Geomorphologic map were produced to show the karst formation/landform present in study area. Limestone karst is a unique landscape with attractive features and has their own type. The karst formation at Kampung Kala Baru has great potential use for geologist and other professional discipline since it offers diversified application such as cave tourism and hydrogeology.